Tectonic Geomorphology of Ultramafic Complex in Asera, North Konawe Regency - Faturrakhman, Muhammad Luthfi; Dian Novita; Akbar Cita; Rohman; Inge Triguri (Jurnal Geologi dan Sumberdaya Mineral, 2024)
Ultramafic complex in Sulawesi have many potential from mining to environmental aspects. The process of weathering and tectonic is a key factor in understanding how to utilize these potential. Tectonic geomorphology by using morphometric indices and field observation has proven to be a beneficial method in distinguishing the topography and morphogenetic development of a region due to the complex interaction between erosional processes and tectonic movements. IAT measurement of 71 sub-basins shows that tectonic activity in the research area are divided into 4 classes with values ranging from 1,5 – 2,6. Field observation shows that morphologically the research area are faulted hills consist of peridotite, dunite and pyroxenite with various degree of weathering. The effect of weathering also reveal on the shape of sub-basins and drainage density in the research area. Tectonic activity present in the form of intensive joint on some parts, with no clear correlation with IAT Class. keyword: tectonic geomorphology, carbon capture storage, ultramafic, east Sulawesi ophiolite, morphometric indices